Crisis Management, School Leadership in Disruptive Times and the Recovery of Schools in the Post COVID-19 Era: A Systematic Literature Review - Paraskevi Chatzipanagiotou; Eirene Katsarou (MDPI AG, 2023)
Contemporary school leadership has always been considered to be one of the most pivotal factors conducive to school effectiveness as well as a driver of change and strategic innovation involving the development of a strong vision, attendant goals and a relevant plan for implementation, monitoring and review. However, the disruption in the provision of educational services caused by the recent COVID-19 pandemic global outbreak revealed deficits in school leadership theory that were largely associated with the adoption of proper crisis management skills by the vast majority of schools' principals to readily adapt to a new reality and effectively confront upcoming challenges, at both instructional and organizational levels. Interestingly, although crisis management as a notion has been substantially elaborated on a theoretical level and successfully applied in different types of crises, it still has not gained a sustained focus within the field of educational leadership, as evidenced by the notable scarcity of related empirical research. This study addresses this gap in the research via a systematic review of scientific papers, published within the 2019-2022 timespan and compiled under the PRISMA framework, reporting on the challenges faced, the crisis management strategies employed and the personality traits that were most commonly associated with effective crisis leadership throughout the turbulent COVID-19 era.